2021
DOI: 10.15678/eber.2021.090210
|View full text |Cite
|
Sign up to set email alerts
|

Nascent entrepreneurs of millennial generations in the emerging market of Indonesia

Abstract: The objective of the article is to investigate the empirical linkages between personality, cultural values, and entrepreneurial characteristics and entrepreneurial behaviour in the context of SMEs' run by millennial generations in Indonesia. Research Design & Methods:This study used survey methods to reveal the relationship between variables through hypotheses testing on 551 respondents from among SMEs' owners who just started business (nascent entrepreneur) in Banjarmasin, Indonesia, with the use of structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
(64 reference statements)
0
16
0
3
Order By: Relevance
“…First, while previous studies have shown that entrepreneurship education promotes entrepreneurial intention (Hahn et al, 2019;Lv et al, 2021), this study empirically explored the moderating mechanism of this relationship by revealing the negative role of proactive personality and the positive role of family economic status. Both entrepreneurship education (Souitaris et al, 2007;Solomon et al, 2019;Muñoz et al, 2020) and the important entrepreneurial characteristics (Becherer and Maurer, 1999;Fairlie and Holleran, 2012;Neneh, 2019;Basuki et al, 2021) are the driving forces of entrepreneurial intention. This study suggests that these two driving forces interact in a negative way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, while previous studies have shown that entrepreneurship education promotes entrepreneurial intention (Hahn et al, 2019;Lv et al, 2021), this study empirically explored the moderating mechanism of this relationship by revealing the negative role of proactive personality and the positive role of family economic status. Both entrepreneurship education (Souitaris et al, 2007;Solomon et al, 2019;Muñoz et al, 2020) and the important entrepreneurial characteristics (Becherer and Maurer, 1999;Fairlie and Holleran, 2012;Neneh, 2019;Basuki et al, 2021) are the driving forces of entrepreneurial intention. This study suggests that these two driving forces interact in a negative way.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of education are determined by the characteristics of the individuals who are educated (Ganzach and Gotlibovski, 2014), such as their personalities (Williamson, 2021). Many studies emphasize the significance of personality in entrepreneurship (Ciavarella et al, 2004;Hisrich et al, 2007;Fairlie and Holleran, 2012;Basuki et al, 2021). Among these, proactive and narcissistic personalities have attracted increasing attention in academia (Bateman and Crant, 1993;Liu et al, 2019;Neneh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Sarwoko and Nurfarida (2021) talk about the so-called entrepreneurial marketing as the primary and direct factor influencing the effectiveness of entrepreneurial activities, and entrepreneurial personality traits are only needed to support this process. Furthermore, Basuki et al (2021) point out that the entrepreneur's cognitive profile is changing significantly under the influence of digital technologies (e.g., the millennial generation). It therefore raises some doubts about the relevance of seemingly obvious socio-demographic and psycho-cognitive factors for internationalization.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Numerous research and empirical evidence in domestic entrepreneurship (e.g. Sarwoko & Nurfarida, 2021;Basuki et al, 2021;Reissová et al, 2020) inclined us to search for the answer to the question how these issues take place, whether they manifest themselves in international entrepreneurship. As these are new ventures or born globals that are the emanation of entrepreneurship in international business, internationalization pace, that is the speed of the internationalization of firms, became our research interest.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of high status for academic brilliance is proven by being ranked highly on the yearly issued world ranking while displaying excellence on outside earnings, which has caused many Indonesian universities to become entrepreneurial universities (Basuki et al, 2021). In this supply-demand state, no surprise that lecturers are gradually more depressed, discouraged, and disconnected from their universities.…”
Section: Introductionmentioning
confidence: 99%